Morphology and Physical Properties of Hydrophilic-Polymer-Modified Lipids in Supported Lipid Bilayers - Kakimoto, Yasuhiro; Tachihara, Yoshihiro; Okamoto, Yoshiaki; Miyazawa, Keisuke; Fukuma, Takeshi; Tero, Ryugo (Langmuir, 2018)
Lipid molecules such as glycolipids that are modified with hydrophilic biopolymers participate in the biochemical reactions occurring on cell membranes. Their functions and efficiency are determined by the formation of microdomains and their physical properties. We investigated the morphology and properties of domains induced by the hydrophilic-polymer-modified lipid applying a polyethylene glycol (PEG)-modified lipid as a model modified lipid. We formed supported lipid bilayers (SLBs) using a 0–10 mol % range of PEG-modified lipid concentration (C PEG). We studied their morphology and fluidity by fluorescence microscopy, the fluorescence recovery after photobleaching method, and atomic force microscopy (AFM). Fluorescence images showed that domains rich in the PEG-modified lipid appeared and SLB fluidity decreased when C PEG ≥ 5%. AFM topographies showed that clusters of the PEG-modified lipid appeared prior to domain formation and the PEG-lipid-rich domains were observed as depressions. Frequency-modulation AFM revealed a force-dependent appearance of the PEG-lipid-rich domain.